Does Social Performance Really Lead to Financial Performance? Accounting for Endogeneity - Garcia-Castro, Roberto (Journal of business ethics, 2010)
The empirical relationship between a firm’s social performance and its financial performance is still not well established in the literature. Despite more than 30 years of research and more than 100 empirical studies on the issue, the results are still mixed. We argue that the heterogeneous results found in previous studies are not due exclusively to problems related with the measurement instruments or the samples used. Instead, we posit that a more fundamental problem related with the endogeneity of social strategic decisions could be driving most of the empirical findings. We show that, using a panel data of 658 firms from 1991 to 2005, how some of the results found in previous research change, and some are even reversed when endogeneity is properly taken into account.